2006
DOI: 10.1007/s10620-006-3146-7
|View full text |Cite
|
Sign up to set email alerts
|

Can Endoscopic Ultrasonography Differentiate Nonneoplastic from Neoplastic Gallbladder Polyps?

Abstract: The present study aimed to clarify the endoscopic ultrasonography (EUS) features of nonneoplastic (cholesterol polyps and adenomyomatosis) and neoplastic (adenoma and adenocarcinoma) gallbladder polyps and to evaluate the effectiveness and limitation of EUS in the differential diagnosis of these lesions. We retrospectively compared EUS images with histologic findings in 29 surgical cases with gallbladder polyps with a diameter of 10 to 20 mm. Those cases were indicated for surgery based on the findings of a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 17 publications
1
27
0
1
Order By: Relevance
“…There are several studies that endoscopic ultrasonography (EUS) has improved accuracy of the differential diagnosis of GB polyps. 6,7,9,27,28 Since this was a retrospective study, some of the patients underwent EUS and we could not evaluate as uniform diagnostic modalities. However, there are many common factors that could predict malignant GB polyps.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies that endoscopic ultrasonography (EUS) has improved accuracy of the differential diagnosis of GB polyps. 6,7,9,27,28 Since this was a retrospective study, some of the patients underwent EUS and we could not evaluate as uniform diagnostic modalities. However, there are many common factors that could predict malignant GB polyps.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports showed that polypoid lesion is highly likely to be cancerous if it is sessile and/or solitary, its diameter is equal to or greater than 10 mm, patient's age is equal to or greater than 60 years old, and/or it grows rapidly [28][29][30][31][32]. According to these results, when polypoid lesion of the gallbladder is sessile, has a diameter equal to or greater than 10 mm and/or grows rapidly, it is highly likely to be cancerous and should be resected by cholecystectomy [28][29][30][31][32][33][34][35][36].…”
Section: Cq2: Is a Cholecystectomy Necessary For Polypoid Lesions Of mentioning
confidence: 99%
“…It is well known that the size of a GB polyp is related to malignancy. Many studies have reported that a GB polyp ≥ 10 mm has a high risk of being a malignancy and this size is one of the criteria for surgical intervention [4,[11][12][13] . However, we also have observed that a benign polyp, such as a cholesterol polyp, can be as large as 10 mm.…”
Section: Discussionmentioning
confidence: 99%